Patterning of polymer brushes made easy using titanium dioxide: direct and remote photocatalytic lithography. Issue 34 (30th March 2015) - Panzarasa, G.; Soliveri, G.; Sparnacci, K.; Ardizzone, S.
Abstract : Titanium dioxide photocatalytic lithography of initiator functionalized surfaces is proved for the realization of micropatterned polymer brushes. Abstract : Photocatalytic lithography is proved for the realization of micropatterned polymer brushes. Initiator-functionalized titanium dioxide or silicon surfaces are respectively exposed directly to near-UV light through a photomask (direct approach) or through a transparent photoactive TiO2 film (remote approach). Initiator patterns are then amplified as polymer brushes with SI-ATRP. Features down to 10 μm could be obtained using simple equipment. The process is intrinsically parallel, has high throughput and scalable to wafer size, making it powerful for microfabrication purposes.